The Effect of Boredom Proneness, Impulsiveness and Sensation Seeking to Driver Speeding Behavior - Leksmono Suryo Putranto; Anissa Noor Tajudin; Sunu Bagaskara (Communications - Scientific letters of the University of Zilina, 2022)
Speeding or driving above the speed limit might be conducted due to various reasons. This paper is intended to investigate whether there are certain underlying behaviors that trigger speeding in the various driving environment. Authors were investigating the effect of boredom proneness, impulsiveness and sensation seeking on driver speeding behaviors. They received 676 responses to our distributed online questionnaires mainly from Lampung, East Java, East Borneo, North Celebes and North Moluccas. A Structural Equation Modelling (SEM) was conducted for analysis. The result implies that the drivers with high sensation seeking, low boredom proneness and high impulsiveness tend to drive at high speed.